Association Between Oral Health Literacy and Number of Remaining Teeth Among the Thai Elderly: A Cross-Sectional Study - Sermsuti-anuwat N; Piyakhunakorn P (Dove Medical Press, 2021)
Nithimar Sermsuti-anuwat,1 Panat Piyakhunakorn2,3 1Faculty of Dentistry, Chulalongkorn University, Bangkok, Thailand; 2Master of Science Program in Geriatric Dentistry and Special Patients Care (International Program), Faculty of Dentistry, Chulalongkorn University, Bangkok, Thailand; 3Panare Hospital, Dental Public Health Division, Pattani, ThailandCorrespondence: Nithimar Sermsuti-anuwatFaculty of Dentistry, Chulalongkorn University, 34 Henri-Dunant Road, Wangmai, Pathumwan, Bangkok, 10330, ThailandTel +66 2218-9016Fax +66 2218-9021Email nithimar.s@chula.ac.thPurpose: Limited oral health literacy is associated with poor oral health status. This study aimed to determine the association between oral health literacy (OHL) and the number of remaining teeth (NRT) among Thailand’s older population.Patients and Methods: This cross-sectional study was conducted between July 1, 2020 and September 30, 2020 at the Subdistrict Health Promoting Hospitals in Panare, Pattani, Thailand. A total of 361 independent-living older adults, male and female, participated in the study. OHL data were obtained using the Thai version of Health Literacy in Dentistry (HeLD‐Th) questionnaire. Trained interviewers performed face-to-face interviews for oral health-related behavior information. The NRT was collected through intraoral examination by a trained examiner. Data were analyzed using SPSS version 22. Mann–Whitney U-tests, chi-square tests, and binary logistic regression analysis were performed. A multivariate logistic regression model was developed to test associations between OHL and NRT and other potential covariates. All analyses were two-sided with a 95% confidence interval.Results: There were significant associations between limited OHL and fewer than 20 remaining teeth (odds ratio [OR]=1.986, P = 0.018), older age (OR=1.743, P = 0.023), and lower educational levels (OR=2.365, P = 0.007).Conclusion: The significance of this evidence is that OHL influences NRT among older Thai people who have lower education levels. Therefore, OHL intervention is an essential strategy for better oral health-related behaviors to reduce tooth loss and to improve the oral health status of Thai older adults.Keywords: oral health, geriatrics, oral health literacy, number of remaining teeth